Echinomycin-induced hypersensitivity to osmium tetroxide of DNA fragments incapable of forming Hoogsteen base pairs. - McLean, M J (1989)
To show conclusively that the critical structural deformation of double-helical DNA that is induced by the binding of quinoxaline antibiotics does not involve the formation of Hoogsteen base pairs, we have prepared a DNA fragment containing the nucleoside analog 7-deaza-2'-deoxyadenosine in one of the two strands. This DNA fragment was subjected to treatment with the thymidine-specific reagent osmium tetroxide and to DNase I "footprinting" in the presence or absence of micromolar concentrations of echinomycin. We report that this anti-tumor antibiotic binds to DNA containing the nucleoside analog as well as to natural DNA and that the previously reported hypersensitivity to osmium tetroxide of certain thymidine residues adjacent to echinomycin binding sites is maintained in analog-containing DNA. Since these thymidines are rendered incapable of participating in Hoogsteen base pairs by the incorporation of 7-deaza-2'-deoxyadenosine, we conclude that this unusual base-pairing scheme is not the cause of the observed hypersensitivity to osmium tetroxide and that it therefore results from a large local unwinding of the DNA in the presence of the antibiotic. Moreover, preventing the possibility of Hoogsteen base pairing does not preclude echinomycin binding.